Ag[B(SO4)2] – Synthesis, Crystal Structure, and Characterization of the First Precious‐Metal Borosulfate. Issue 34 (13th July 2017) - Bruns, Jörn; Podewitz, Maren; Schauperl, Michael; Liedl, Klaus R.; Janka, Oliver; Pöttgen, Rainer; Huppertz, Hubert
Abstract : The reaction of Ag(NO3 ) with H3 BO3 in oleum (20 % SO3 ) yielded single crystals of Ag[B(SO4 )2 ] [tetragonal, P 4/ ncc, Z = 4, a = 8.6679(5) Å, c = 7.2897(5) Å, V = 547.69(7) Å 3 ]. In Ag[B(SO4 )2 ], infinite anionic chains, according to the Niggli formula ∞ 1 [B(SO4 )4/2 ] –, are found in tetragonal‐rod packing with charge compensation by Ag I cations. The chains are built by central boron atoms coordinated through oxygen atoms to four bidentate bridging SO4 tetrahedra. Terminal oxygen atoms of the SO4 tetrahedra coordinate to the silver cations in the form of slightly distorted square prisms. Magnetochemical investigations reveal the expected closed‐shell behavior of d 10 cations. DFT investigations of the solid‐state structure corroborate the experimental findings and permit the assignment of vibrational spectroscopic data. Abstract : The first precious‐metal borosulfate is obtained under harsh conditions. The reaction of Ag(NO3 ) with H3 BO3 in oleum leads to Ag[B(SO4 )2 ]. Single‐crystal X‐ray diffraction reveals tetragonal packing of Ag I cations and infinite chains of [B(SO4 )2 ] – anions. XRD, IR and Raman spectroscopic, and magnetochemical measurements were performed and further corroborated by means of quantum‐chemical studies.